1999
DOI: 10.1046/j.1464-410x.1999.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

The management of vesical calculi with combined optical mechanical cystolithotripsy and transurethral prostatectomy: is it safe and effective?

Abstract: Objectives To investigate the eCectiveness and reliabilityResults The mean duration of surgery, hospital stay and urethral catheterization were significantly longer with of the combination of optical mechanical cystolithotripsy (OMC) and transurethral prostatectomy (TURP) combined OMC and TURP than with OMC alone (P<0.05). Stone-free rates were 94% after OMC alone for the treatment of bladder calculi and obstructive benign prostatic enlargement (BPE).and 93% after combined OMC and TURP. The postoperative mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 17 publications
0
27
0
1
Order By: Relevance
“…The AUA symptom score, peak urinary flow rate (Q max ) and PVR was significantly improved at 1 month after surgery (Table 2) and these immediate improvements persisted for a year (Table 1 and 2), being significant for each variable ( P < 0.001). A review of previously reported cases managing vesical calculi with associated BOO is presented in Table 2[1,6–21].…”
Section: Resultsmentioning
confidence: 99%
“…The AUA symptom score, peak urinary flow rate (Q max ) and PVR was significantly improved at 1 month after surgery (Table 2) and these immediate improvements persisted for a year (Table 1 and 2), being significant for each variable ( P < 0.001). A review of previously reported cases managing vesical calculi with associated BOO is presented in Table 2[1,6–21].…”
Section: Resultsmentioning
confidence: 99%
“…It has an added advantage as it can be combined with a corrective procedure for bladder outlet obstruction. [11] Electrohydraulic shockwave lithotripsy (EHSWL) is preferably to be avoided in hard, large vesical calculi and if the stone is in a diverticulum or stuck to the mucosa. [12] Conclusion A giant vesical calculus more than 100 gm is rare entity.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…Surgical treatment of vesical calculus has evolved over years from blind insertion of crushing forceps into the bladder, to open surgical removal or extra corporeal fragmentation, cystolithotripsy and percutaneous cystolithotripsy out of whichopen surgery has been the best recommended modality for large stones 6 . In small or moderate calculus endourological procedures such as cystolithotripsy has an added advantages as it can be combined with corrective procedure for bladder outlet obstruction 7 . Zhaowll et al have recommended that electrohydraulic shock wave lithotripsy preferably to be avoided in the large hard vesical calculus and if the stone is in the diverticulum or stuck to the mucosa as chances of bladder perforation is high 8 .…”
Section: Case Reportmentioning
confidence: 99%